Analysis of clickbaiting in contemporary Spanish press headlines/ A case study: "El País" on Facebook - García Serrano, Jesús; Romero-Rodríguez, Luis M.; Hernando Gómez, Ángel (Estudios sobre el Mensaje Periodístico, 2019)
The quality of digital journalism is currently at risk due to the extreme competence for attracting traffic from the social networks. Thus, it is becoming increasingly more frequent to include appealing headlines, which are sometimes not rigorous enough, as bait (clickbaiting). This fact could result in a distortion of reality and can contribute to a process of general misinformation. This research analyses, both quantitatively and qualitatively, and in an exploratory way, the appearance of the clickbaits in the Facebook fan page of Elpais.com in n=167 informative units. The study reveals the existence of some sort of clickbait in more than half of the sample -which, moreover, goes against the journal’s policy-, especially that of the omissive kind, an item for which a new subcategorization has been established. In the same way, a significant lack of concordance has been detected between the information contained in some headlines and that included in the rest of the article.